(untitled) (Scientific journal of the Fergana State University, 2025)
The article explores key aspects of metalinguistics, including the concepts of metalanguage, metatext and metacommunication. The main attention is paid to lexical and grammatical indicators used in metacommunicative speech acts, such as introductory constructions, verbs of intention and correction, negative particles, interrogative constructions and evaluative adjectives. Examples from S. Dovlatov’s work «Pushkin Hills» [2] illustrate the theoretical provisions. The research methods include an analysis of the existing literature and a qualitative analysis of examples of metacommunication. The aim of the research is to gain an in-depth understanding of the mechanisms of human communication through the analysis of metacommunicative processes, the definition and classification of the basic concepts of metalinguistics, as well as the identification and description of metacommunicative conflicts, their causes and ways of resolution. Understanding these aspects helps to improve communication skills and prevent misunderstandings in communication.